Osimertinib as first-line treatment for advanced epidermal growth factor receptor mutation–positive non–small-cell lung cancer in a real-world setting (OSI-FACT). (December 2021) - Sakata, Yoshihiko; Sakata, Shinya; Oya, Yuko; Tamiya, Motohiro; Suzuki, Hidekazu; Shibaki, Ryota; Okada, Asuka; Kobe, Hiroshi; Matsumoto, Hirotaka; Yokoi, Takashi; Sato, Yuki; Uenami, Takeshi; et al.
Abstract: Background: Osimertinib is the standard of care in the initial treatment for advanced epidermal growth factor receptor (EGFR) mutation–positive lung cancer. However, clinical data and reliable prognostic biomarkers are insufficient. Methods: We performed a retrospective multicentre cohort study for 538 EGFR mutation–positive patients, who received osimertinib as the initial treatment between August 2018 and December 2019. The main outcome was progression-free survival (PFS). Results: The median observation period was 14.7 months (interquartile range 11.4–20.0). The median PFS was 20.5 months (95% confidence interval [CI] 18.6−not reached). Multivariate analysis showed that sex (male) (hazard ratio [HR] 1.99, 95% CI 1.35–2.93, P  = 0.001), malignant effusions (HR 1.51, 95% CI 1.11–2.04, P  = 0.008), liver metastasis (HR 1.55, 95% CI 1.03–2.33, P  = 0.037), advanced unresectable cases (HR 1.71, 95% CI, 1.04–2.82, P  = 0.036), mutation type and programmed cell death-ligand 1 (PD-L1) expression were associated with PFS. The L858R (HR 1.55, 95% CI 1.01–2.38, P  = 0.043) and uncommon mutations (HR 3.15, 95% CI 1.70–5.83, P  < 0.001) were associated with PFS. PD-L1 expression of 1–49% (HR 1.66, 95% CI 1.05–2.63, P  = 0.029), ≥50% (HR 2.24, 95% CI 1.17–4.30, P  = 0.015) and unknown (HR 1.53, 95% CI 1.05–2.22, P =  0.026) was associated with PFS. The main reasons for treatment discontinuation among 219 patients were disease progression (44.3%), pneumonitis (25.5%) and other adverse events (16.0%). Conclusion: During initial treatment with osimertinib, PD-L1 expression is significantly related to PFS. Adverse events are a noteworthy reason for discontinuation. Highlight: Osimertinib is standard treatment for advanced EGFR mutation-positive lung cancer. Clinical data and reliable prognostic biomarkers remain insufficient. Tumour PD-L1 expression level is associated with progression-free survival. Adverse events are a common reason for treatment discontinuation.